Proceedings of the Fifth International Seminar on English Language and Teaching (ISELT 2017) 2017
DOI: 10.2991/iselt-17.2017.36
|View full text |Cite
|
Sign up to set email alerts
|

The Language Interference in English Speaking Skill for EFL Learners

Abstract: Abstract-This paper examines the language interference in English speaking skill. The interference was influenced by the mother tongue of the learners. Therefore, this study explains the forms of language interference in the students' speaking skill and the factors affecting the language interference. In addition, the study attempts to use case study with descriptive qualitative research approach. The data were collected by using the questionnaire and recording technique. The data, then, were analyzed based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…Pronunciation simplifies organized sounds of language produced by human speech organs using all the phonemic units of the language (Labov as cited in Subandowo, 2017). According to Stefani, Basri, & Josep (2015) pronunciation is an essential language part of communication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pronunciation simplifies organized sounds of language produced by human speech organs using all the phonemic units of the language (Labov as cited in Subandowo, 2017). According to Stefani, Basri, & Josep (2015) pronunciation is an essential language part of communication.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this idea, Risdianto (2017) also said that different phonemes between the mother tongue and the English language are the nature of pronunciation problems. Subandowo (2017) mentions that the students' mother tongue interference the students to pronounce the English words, besides students' motivation and different sounds, and different sounds symbol was a problem of students to pronounce the English words. Aulia (2018) founds that the mother tongue becomes the main problem that strongly affects the production of students' pronunciations.…”
Section: Introductionmentioning
confidence: 99%
“…The reason behind this situation is because of students' ability to understand complex sentence translation level in paragraphs is still quite difficult and unable to translate it well. The students or translator must master the language pairs, the source language, and the target language (Subandowo, 2017). But, in the fact, most of them are difficult to translate English into Indonesian well and make errors when they translate in the translation subject.…”
Section: Introductionmentioning
confidence: 99%
“…Cook (2001), Denizer (2017) and Pathan et al (2014) also found the same problems in getting students to talk in the classroom. Furthermore, Subandowo (2017) and Gani et al (2015) found that students had problems with proper pronunciation, while Melendez et al (2014) and Gani et al (2015) found that many students lacked an adequate vocabulary and had poor skills with grammar. Next, Savaşçı (2014), Machmud and Abdulah (2017), Yalçın and İnceçay (2014), Kayaoğlu and Sağlamel (2013), and Machmud and Abdulah (2018) said that many students tend to be passive during class because they are too frightened to speak because of speaking anxiety.…”
Section: Introductionmentioning
confidence: 99%